Creatine supplementation and oxidative stress in rat liver - Araujo, Michel B. [UNESP]; Moura, Leandro P. [UNESP]; Vieira Junior, Roberto C.; Junior, Marcelo C. [UNESP]; Dalia, Rodrigo A. [UNESP]; Sponton, Amanda C. [UNESP]; Ribeiro, Carla [UNESP]; Mello, Maria Alice R. [UNESP] (Biomed Central Ltd., 2013)
Background: The objective of this study was to determine the effects of creatine supplementation on liver biomarkers of oxidative stress in exercise-trained rats.Methods: Forty 90-day-old adult male Wistar rats were assigned to four groups for the eight-week experiment. Control group (C) rats received a balanced control diet; creatine control group (CCr) rats received a balanced diet supplemented with 2% creatine; trained group (T) rats received a balanced diet and intense exercise training equivalent to the maximal lactate steady state phase; and supplemented-trained (TCr) rats were given a balanced diet supplemented with 2% creatine and subjected to intense exercise training equivalent to the maximal lactate steady state phase. At the end of the experimental period, concentrations of creatine, hydrogen peroxide (H2O2) and thiobarbituric acid reactive substances (TBARS) were measured as well as the enzyme activity of superoxide dismutase (SOD), glutathione peroxidase (GSH-GPx) and catalase (CAT). Liver tissue levels of reduced glutathione (GSH), oxidized glutathione (GSSG) and the GSH/GSSG ratio were also determined.Results: Hepatic creatine levels were highest in the CCr and TCr groups with increased concentration of H2O2 observed in the T and TCr animal groups. SOD activity was decreased in the TCr group. GSH-GPx activity was increased in the T and TCr groups while CAT was elevated in the CCr and TCr groups. GSH, GGS and the GSH/GSSG ratio did not differ between all animal subsets.Conclusions: Our results demonstrate that creatine supplementation acts in an additive manner to physical training to raise antioxidant enzymes in rat liver. However, because markers of liver oxidative stress were unchanged, this finding may also indicate that training-induced oxidative stress cannot be ameliorated by creatine supplementation.
Keywords: Creatine supplementation; Oxidative stress; Enzymes; Treadmill exercise